2008
DOI: 10.1007/s11069-007-9190-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of reconstructed geomorphologic units in landslide susceptibility mapping: the Melen Gorge (NW Turkey)

Abstract: In the international literature, although considerable amount of publications on the landslide susceptibility mapping exist, geomorphology as a conditioning factor is still used in limited number of studies. Considering this factor, the purpose of this article paper is to implement the geomorphologic parameters derived by reconstructed topography in landslide susceptibility mapping. According to the method employed in this study, terrain is generalized by the contours passed through the convex slopes of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Actually, this suggestion directly points out the necessity to determine the pre-failure conditions of landslides because it is not always possible to reach exact topographical conditions at the time of landslide occurrence in particular. However, few studies investigating this research topic have been published in recent literature (Suzen and Doyuran 2004;Clerici et al 2006;Gorum et al 2008;Nefeslioglu et al 2011). For this reason, research into the determination of the pre-failure conditions of landslides remains crucial in spite of its limitations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, this suggestion directly points out the necessity to determine the pre-failure conditions of landslides because it is not always possible to reach exact topographical conditions at the time of landslide occurrence in particular. However, few studies investigating this research topic have been published in recent literature (Suzen and Doyuran 2004;Clerici et al 2006;Gorum et al 2008;Nefeslioglu et al 2011). For this reason, research into the determination of the pre-failure conditions of landslides remains crucial in spite of its limitations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Nefeslioglu et al (2008) stated that the conceptual differentiation of different sampling strategies applied during susceptibility evaluations is commonly ignored and is no longer event stated. In the literature, a few researchers (Suzen and Doyuran 2004;Clerici et al 2006;Gorum et al 2008;Nefeslioglu et al 2008;Yilmaz 2010;Nefeslioglu et al 2011) have taken differences in sampling strategies into account and have suggested different sampling strategy methods in their studies. Suzen and Doyuran (2004) proposed a seed cell sampling strategy, creating buffer zones to the crown and the flanks of landslides; Clerici et al (2006) suggested a shell script and took into account selected factor cells defined on the upper edge of the main scarps of landslides; Gorum et al (2008) concluded the utility of geomorphological parameters derived from the reconstructed topography, and Nefeslioglu et al (2011) proposed a sampling circle approach for determination of the conditioning factors of shallow and small sized landslides that cannot be mapped at medium scale.…”
Section: Introductionmentioning
confidence: 99%
“…Databased bivariate and multivariate statistical analysis methods were studied about landslides (Suzen and Doyuran, 2004a). Geomorphological parameters were also used to determine landslide susceptibility maps and properties (Gorum et al, 2008). Another study is conducted to investigate the parameter effects in preparing landslide susceptibility maps with a data-driven approach and adaptation of this approach to analytical hierarchy process (AHP) (Hasekiogullari and Ercanoglu, 2012).…”
Section: Characteristics Of the Study Areamentioning
confidence: 99%
“…Considering the extent of the study area and the areal distribution of the shallow landslides, the mapping unit for the study was selected as grid cells with a spatial resolution of 10×10 m 2 (100 m 2 ). In the event that areal mapping of landslides can be established, different approaches from recent literature (Suzen and Doyuran 2004;Clerici et al 2006;Gorum et al 2008) can be applied to extract pre-failure conditions. However, there has been no suggestion in the literature to extract conditioning factors in cases where areal 1990; b 1990-2000; c 2000-2004; d 2004-2007 Original Paper…”
Section: Temporal Shallow Landslide Inventorymentioning
confidence: 99%